Money supply and the policy of financing public investments in Algeria: An econometric study for the period (1990-2023) - Aidouni, Halima; Boudellal, Ali; Ismail, Morad (The International tax journal, 2025)
This study aims to analyze and measure the impact of money supply on investment financing in Algeria during a specific time period (1990-2023), using the Autoregressive Distributed Lag (ARDL) model relying on official annual data processed through Eviews 12 software. The findings reveal that money supply does not significantly affect investment in Algeria in the long term, while a dynamic relationship exists betwen the two variables in the short term. This outcome can be explained by the nature of the Algeria’s economy, where public investment financing primarily relies on state treasury funds, consequently, investment levels are more influenced by oil prices and GDP growth than by various monetary policy instruments.